Diversity of anthocyanin and proanthocyanin biosynthesis in land plants - Saigo, Tomoki; Wang, Tong; Watanabe, Mutsumi; Tohge, Takayuki (Current opinion in plant biology, 2020)
Anthocyanins and proanthocyanidins are among the most numerous and widely distributed pigments in land plants. Given that these pigments are the valuable compounds, as stress protectants and health-promoting components because of their potent antioxidant activity, several metabolic engineering approaches focusing on these compounds have been attempted. Currently, the difference in biological functions between flavonoid decorations is focused, because some aglycone decorations were found to be key factors rendering physiological functions against environmental stresses. Therefore, metabolic diversity and functional genomics approaches focusing on anthocyanin decoration should be reconsidered. Additionally, since the production of anthocyanins and proanthocyanidins in plants is often represented in a tissue-specific manner and by stress induction, elucidation of the specific regulatory mechanisms of how these pathways have been evolved, is highly important. Here, we review current knowledge of the diversity of chemical structure and regulators of anthocyanin/proanthocyanin biosynthesis with cross-species comparison to assess metabolic evolution.